Application of Reading Strategy as an Effort to Develop a Confident Attitude of K1 Private School Students in Daan Mogot from a Biblical Point of View - Silaban, Paulina Deborah; Cendana, Wiputra (Universitas Tanjungpura, 2024)
The research is to enhance the self-confidence of K1 students at Daan Mogot Private School through the implementation of reading strategies. The low level of students' self-confidence negatively impacts their participation. This research is important because self-confidence is a key factor in academic success and student character development. The research method is a descriptive qualitative approach, which involves participatory observation, semi-structured interviews with teachers, and document studies. The research results show that the application of reading strategies has a significant positive impact on the increase in students' self-confidence. Before the implementation of the strategy, only 9% of students showed high confidence. However, after the implementation, 63% of students began actively asking and answering questions, reflecting a substantial increase in student confidence. Reading strategies not only enhance students' academic abilities but also contribute to the development of their character and self-confidence. Thus, the implementation of reading strategies based on biblical values can be an effective solution to address the issue of low self-confidence among K1 students, as well as support them in facing future challenges. This research is expected to serve as a reference for educators in designing more effective learning methods that focus on the character development of students.